“Efecto de las fases lunares en la injertación y prendimiento de yemas usando el clon ccn-51, en el cultivo del cacao (theobroma cacao L.) en tarapoto-San Martín” - Flores Torres, José Antonio (2013)
The present wark of investigation titled "Effects of the Lunar Phases in the graftining and Capture of Yalks in the Cultivate af Cacaa (Theobroma cocoa L.), Using the Clan CCN - 51". Developed on the property af Mr. Antonio Paredes Flores, located District of Morales bottom area 3 km. city of Tarapoto, San Martin province. Start af work an May 28, 2011 through May 12, 2012, using the (DBCA), "Design of a randomized complete block", with 4 treatments and 4 blocks. For the production af seedlings was used Pound variety seed, planting took place in the early hours of the morning, after 6 months of age was canducted grafting central pin type which was used far the yolks rods Clone CCN - 51. The parameters studied were. P.ercent engraftment (%), base diameter of the plant stem, plant height (cm) and gra~ed height, number of leaves af the plant befare and after making graft (cm), 1 number of lit plants, number of autbreaks in grafted plants and lit, leaf number graft plant. The results indicate that the plant height (cm), number of leaves, engraftment, number of shoots graft and graft height graft leaf number were determinad to synchronize with higher yield in moles phases Full Moan and Moon Faurth Quarter, determinedly. Key words: Lunar Phases, grafting, Clone, Seedlings, outbreaks, Yolk.